MANAJEMEN KORESPONDENSI PADA BAGIAN UMUM DAN KEPEGAWAIAN DI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SUBANG - Wahid, Yenita Nur; Silliya, Najma; Prahardik, Septian Eka; Aini, Nurul; Farihin, Ahmad; Khuludiyah, Putri (STAIN Madina Press, 2025)
A letter is a communication tool used to convey written information from one party to another. The management of the administrative section, especially correspondence, is very important for an organization. The main objective of this research is to examine the issues of letter management and the handling provided at the Subang Education and Culture Office. This research uses a qualitative approach, which aims to thoroughly understand how each stage of the process (such as document creation, management, and archiving) is carried out in the Subang Education and Culture Office. in managing correspondence, the process is quite systematic, although there are still some obstacles that need to be addressed to improve efficiency. The conclusion of this research is that the management of correspondence at the Education and Culture Office of Subang Regency has been carried out in a structured manner, covering the processes of recording, disposition, distribution, and archiving, both for incoming and outgoing letters. Despite some obstacles, the management of correspondence at the Education and Culture Office of Subang Regency is conducted in an organized structure.